CAREER DEVELOPMENT AND WORKLOAD ON TURNOVER INTENTION AT EAST JAVA PROVINCIAL DEPARTMENT OF CULTURE AND TOURISM - Yuni Maulidiyah Dwi Fajar (Journal of Applied Economics in Developing Countries, 2025)
This study aims to examine the effect of career development and workload on job satisfaction, the effect of job satisfaction on turnover intention, and the mediating role of job satisfaction in the relationship between career development and workload on turnover intention. The research focuses on non-permanent employees with work agreements (PTT-PK) at the Department of Culture and Tourism of East Java Province. This quantitative study employed a survey method with a saturated sample of 89 PTT-PK employees registered at the East Java Provincial Civil Service Agency (BKD). Data were collected using an online questionnaire and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS software. The results show that (1) career development has a significant positive effect on job satisfaction, (2) workload has a significant negative effect on job satisfaction, (3) job satisfaction has a significant negative effect on turnover intention, (4) job satisfaction significantly mediates the effect of career development on turnover intention, and (5) job satisfaction does not significantly mediate the effect of workload on turnover intention. These findings highlight the importance of career development and workload management in improving job satisfaction and reducing turnover intention among non-permanent government employees.